EKSPLORASI DINAMIKA STRUKTUR MODAL PADA PT SEMEN INDONESIA (PERSER) TBK - Hamidah, Fina Nur; Hayati, Nur (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research explores the capital structure of PT Semen Indonesia (Persero) Tbk for the period 2019-2023, using qualitative methods and literature review studies. The research focus includes analysis of Debt to Equity Ratio (DER), Liquidity, Profitability (ROA), Total Asset Turnover, Sales Growth, Asset Structure, Net Profit Margin, Company Size, and Business Risk. The data analyzed comes from the company's annual financial statements as well as various other reliable public data sources. The research findings show that DER has decreased significantly, reflecting an increase in the company's financial stability. Although liquidity fluctuates and tends to be below industry standards, ROA is relatively stable with an average of 2.9%, while Total Asset Turnover and Net Profit Margin perform quite well despite being below industry standards. Sales Growth fluctuated significantly, while the company's Asset Structure experienced a decline. Nonetheless, Company Size stabilized with significant total assets, and Business Risk showed moderate fluctuations. This research provides important insights for company management in developing more efficient financial strategies for the future